Ngôn ngữ lạc quan của báo cáo thường niên và tài trợ doanh nghiệp: Bằng chứng tại Việt Nam - Trần Thị Hải , Lý; Lê Thị Phương , Vy; Phùng Đức , Nam (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2019)
This paper aims to examine whether managerial optimism affects the financial leverage of Vietnamese firms by using the data collected over the 2010–2016 period. The authors employ a new approach to measure the managerial optimism which is based on the annual report’s linguistic tone. Using the fixed effects model for panel data, the study finds that firms being operated by optimistic managers have a higher debt ratio and tend to increase external debt financing when they confront financial deficits. These results are consistent with theoretical arguments and previous empirical evidence that corporate financing behavior by optimistic managers follows the pecking-order theory. These results also provide an implication for future researches and financial market that the consideration for corporate financing behavior does not emphasize only on fundamental factors but also managerial psychological traits.
Keywords: Leverage; Managerial Optimism; Linguistic Tone; Annual Report